A review of the genus Lamellipalpodes Maulik (Coleoptera: Lampyridae) - Bocakova, Milada; Bocak, Ladislav; Gimmel, Matthew L.; Friedlova, Tereza (Zootaxa, 2015)
The Ototretinae genus Lamellipalpodes Maulik, 1921 is reviewed. Four species are proposed as new to science, L. bajhangensis Bocakova sp. nov., L. holzschuhi Bocakova sp. nov. and L. godawarensis Bocakova sp. nov., all from Nepal, and L. yunnanensis Bocakova sp. nov. from China (Yunnan) and northern Laos. Six species are redescribed. Illustrations of diagnostic characters are included, with a checklist and a key to Lamellipalpodes species. The genus is newly recorded from China and Laos.